Archaeological applications of microvertebrate analysis : reconstruction of natural and anthropic processes - Kligmann, Débora M. (2015)
Fil: Kligmann, Debora M.. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.